Effect of calorie-restriction and rapamycin on autophagy and the severity of caerulein-induced experimental acute pancreatitis in mice - Sharma, Manish Kumar; Priyam, Kumari; Kumar, Punit; Garg, Pramod Kumar; Roy, Tara Sankar; Jacob, Tony George (Frontiers in Gastroenterology, 2022)
Background Impaired autophagy contributes to development of acute pancreatitis (AP). We studied the effect of inducing autophagy by calorie-restriction and rapamycin, separately, in the caerulein-induced model of severe AP. Methods Adult, male, Swiss albino mice were given eight, hourly, intraperitoneal injections of caerulein (Ce) (50µg/Kg/dose). The interventions were calorie restriction (CR) and rapamycin (2mg/Kg). Mice were sacrificed at the 9th hour. Pancreas was harvested for histopathology and immunoblotting. Amylase activity and the levels of cytokines were measured in plasma. Results The histopathological score and amylase activity were significantly lower in calorie-restricted caerulein-induced AP (CRCeAP) in comparison to animals that had unrestricted access to chow. In the CRCeAP group, levels of IL-6 and GM-CSF in plasma were lower and the expression of LC3II and Beclin-1 were higher. On transmission electron-microscopy, the area occupied by autophagic vacuoles was higher in CRCeAP. The expression of caspase-8 and caspase-9 was also higher in CRCeAP. In rapamycin with caerulein-induced AP (Rapa+CeAP), the histopathological score and amylase activity were significantly lower than caerulein-induced AP (CeAP). In Rapa+CeAP, the expression of LC3II and Beclin-1 were higher, whereas; SQSTM1 was decreased. The number of autophagic vacuoles in Rapa+CeAP group was fewer. Interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and monocyte chemoattractant protein-1 (MCP-1) were lower in Rapa+CeAP. Caspase-3 increased and high mobility group box 1 (HMGB1) decreased in Rapa+CeAP. Conclusion Calorie-restriction and rapamycin can individually decrease the severity of injury in the caerulein-induced model of severe AP.